Asymmetric Total Synthesis of Mycoleptodiscin A1. (23rd April 2015) - Zhou, Shupeng; Chen, Hao; Luo, Yijie; Zhang, Wenhao; Li, Ang
Abstract: The first total synthesis of mycoleptodiscin A, a structurally unusual indolosesquiterpenoid possessing an ortho ‐benzoquinone motif, has been accomplished. A sulfone alkylation coupled two readily available fragments to give an aryl triene intermediate. The tetracyclic core of the molecule was assembled through a highly enantioselective iridium‐catalyzed polyene cyclization. The benzylic homologation was achieved by a cationic cyanation. The indole motif was constructed via a copper‐mediated intramolecular CN bond formation at a late stage.